PENGARUH BEBAN KERJA DAN KONFLIK KERJA TERHADAP TURNOVER INTENTION SERTA DAMPAKNYA TERHADAP STRES KERJA KARYAWAN (STUDI KASUS DI PT.AURORA INDAH ELEKTRIK SUNGGAL) - Emy Wakhyuni, Nashrudin Setiawan, Abdi Setiawan (JURNAL PIONIR, 2021)
Research was conducted to look at how the direct and indirect influence of workload, andwork conflicts to turnover intention through work stress (case study PT.Aurora IndahElectric Sunggal). The population in this study is all employees of PT. Aurora Indah ListrikSunggal numbered 134 employees with the number of samples taken by 101 respondentswhere the number of samples was determined by the formula Slovin. The data used primarydata was taken directly from respondents using questionnaires. This study uses quantitativedata processed with SPSS with path analysis. Path analysis results show workload and workconflicts directly affect positive and significant work stress where the value StandardizedCoefficients Beta workload and work conflicts to work stress by 0.423 and 0.532, by asignificant 0.000, were 0.423 and 0.532, with a significant .000. In addition, workload, workconflict, and work conflict directly also positively and significantly affect turnover intentionwith standardized coefficients beta values of workload, work conflict, and work stress againstturnover intentions consecutively of 0.406, 0.286, and 0.326 with significantly in order of0.000; 0.004, and 0.002. The results of the path analysis also showed that indirectlyworkload and work conflicts did not have a significant influence on turnover intentionsthrough work stress. Indirect influence of workload on turnover intention through work stressby 0.121 which is smaller than the direct influence of 0.406 and indirect influence of workconflict on turnover intention through work stress by 0.152 which is smaller than the directinfluence of 0.286Keywords: Workload, Work Conflict, Work Stress, Turnover Intention.